PENGARUH KEPEMMPINAN, LINGKUNGAN KERJA DAN DAN EFIKASI DIRI TERHADAP MOTIVASI KERJA DI PT. MITRA KARYA LIMA SUKSES - Halawa, Darmanius; Siagian, Nalom; Tobing, Artha L (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2025)
This thesis discusses the influence of leadership, its dynamics and style, along with the work environment and self-efficacy on work motivation. Work motivation can emerge and be maximized if leadership, the work environment, and self-efficacy are implemented effectively. This means that encouraging work motivation at PT. Mitra Karya Lima Sukses requires work motivation. Strong work motivation leads to increased productivity. Therefore, leadership, the work environment, and self-efficacy are the dominant factors in driving work motivation in the company. It can be seen and concluded that a good leadership style and all indicators of excellent leadership significantly improve work motivation